Experts' Encounters in Antenatal Diabetes Care: A Descriptive Study of Verbal Communication in Midwife-Led Consultations - Christina Furskog Risa; Febe Friberg; Eva Lidén (Hindawi Limited, 2012)
Aim. We regard consultations as cocreated communicatively by the parties involved. In this paper on verbal communication in midwife-led consultations, we consequently focus on the actual conversation taking place between the midwife and the pregnant woman with diabetes, especially on those sequences where the pregnant woman initiated a topic of concern in the conversation. Methods. This paper was undertaken in four hospital outpatient clinics in Norway. Ten antenatal consultations between midwives and pregnant women were audiotaped, transcribed to text, and analyzed using theme-oriented discourse analysis. Two communicative patterns were revealed: an expert's frame and a shared experts' frame. Within each frame, different communicative variations are presented. The topics women initiated in the conversations were (i) delivery, time and mode; (ii) previous birth experience; (iii) labor pain; and (iv) breast feeding, diabetes management, and fetal weight. Conclusion. Different ways of communicating seem to create different opportunities for the parties to share each other's perspectives. Adequate responses and a listening attitude as well as an ambiguous way of talking seem to open up for the pregnant women's perspectives. Further studies are needed to investigate the obstacles to, and premises for, providing midwifery care in a specialist outpatient setting.